A New Gilded Age, and What It Means for Global Health; Comment on "Global Health Governance Challenges 2016 - Are We Ready?" - Ted Schrecker (Kerman University of Medical Sciences, 2017)
New contours of global inequality present new challenges for global health, and require that we consider new kinds of health issues as global. I provide a number of illustrations, arguing the need for a political science of health that goes beyond conventional preoccupations with formal institutional and interstate interactions and takes into account how globalization has affected the health policy landscape and restructured the distribution of economic and political power not only among countries, but also within them.